Determining the best strategy to reduce losses in Banias water network, based on the Analytical Hierarchy Process AHP: تحديد الاستراتيجية الأفضل لتخفيف الفواقد في شبكة مياه مدينة بانياس بالاعتماد على طريقة التحليل الهرمي Analytical Hierarchy Process (AHP) - Jamelah Mouhammad Salman, Abbas Abdulrahman (Journal of engineering sciences and information technology, 2021)
The study aims to choose the best strategy for reducing Water losses in Banias City Water Distribution network, that reaches a large percentage about 65%, based on the Analytical Hierarchy Process (AHP).The strategies (alternatives), the main and secondary criteria necessary to reach the construction of the decision matrix and the development of the final strategies for the work of the Establishment in accordance with it, based on the opinions of experts in the Banias Water Establishment, in addition to references and previous studies in the field of research.The necessary questionnaire was prepared and then distributed to a group of experts (30 experts) of engineers and technicians working in Banias Water Establishment, and thus conducting comparison process between the main criteria, the sub- criteria, and the alternatives for the sub- criteria.The Expert Choice Software Which is based on AHP method, is used, and It automatically performs mathematical processes and calculates final relative weights to obtain the final decision matrix. The results showed that the strategy of dividing the network into district metered areas ranked first, with the highest rating of 27.8%, followed by the strategy of control and pressure management with 13.6%, while the strategy of replacing meters came last with 3.5%.